Proteolytic footprinting of transcription factor TFIIIA reveals different tightly binding sites for 5S RNA and 5S DNA. - Bogenhagen, D F (1993)
Transcription factor IIIA (TFIIIA) employs an array of nine N-terminal zinc fingers to bind specifically to both 5S RNA and 5S DNA. The binding of TFIIIA to 5S RNA and 5S DNA was studied by using a protease footprinting technique. Brief treatment of free or bound TFIIA with trypsin or chymotrypsin generated fragments which were separated by sodium dodecyl sulfate-polyacrylamide gel electrophoresis. Fragments retaining the N terminus of TFIIA were identified by immunoblotting with an antibody directed against the N terminus of TFIIIA. Proteolytic footprinting of TFIIIA complexed with 5S DNA derivatives reinforced other evidence that the three N-terminal zinc fingers of TFIIIA bind most tightly to 5S DNA. Proteolytic footprinting of TFIIIA in reconstituted 7S ribonucleoprotein particles revealed different patterns of trypsin sensitivity for TFIIIA bound to oocyte versus somatic 5S RNA. Trypsin cleaved TFIIIA between zinc fingers 3 and 4 more readily when the protein was bound to somatic 5S RNA than when it was bound to oocyte 5S RNA. A tryptic fragment of TFIIIA containing zinc fingers 4 through 7 remained tightly associated with somatic 5S RNA. Zinc fingers 4 through 7 may represent a tightly binding site for 5S RNA in the same sense that fingers 1 through 3 represent a tightly binding site for 5S DNA.